Galvanized RHS X-Connections. I: Effects of vent and drain holes on SCFs. (April 2020) - Daneshvar, Sara; Sun, Min; Karimi, Kian
Abstract: For galvanizing of welded tubular steel trusses, sufficiently large holes to allow for quick filling, venting and drainage must be specified to mitigate the risk of damage. These holes, quite often specified at the hot spot stress locations recommended by the current design guides, will inevitably affect the fatigue behaviour of the connection. In this research, six rectangular hollow section (RHS) connections, with varied hole location and brace-to-chord width ratio, were tested under brace axial loading. The stress concentration factors (SCFs) obtained from the experimental investigation were compared with those calculated using the formulae in CIDECT Design Guide 8. It was shown that the predictions based on the current formulae are unsafe. Hence, finite element (FE) models were developed and validated by comparison with the experimental data. A subsequent parametric study was conducted, including 192 FE models with varied hole location, brace-to-chord width ratio, chord width-to-thickness ratio, and brace-to-chord thickness ratio. Finally, SCF formulae for RHS connections with vent and drain holes at different locations were established based on the experimental and FE data. Highlights: CIDECT Design Guide 8 calculation rules can be unsafe for SCFs in RHS connections with vent and drain holes . 6 connection specimens were tested . 192 FE models were analysed . Modified design rules that consider vent and drain holes are proposed.